The Influence of Creative and Cultural Elements On The Boarding House in Order to Develop an Appropriate Business Model to be Applied at GW Indekost - Wibowo, Gabriella; Larso, Dwi (The Indonesian Journal of Business Administration, 2014)
Abstract - In the world of newcomers business, â€œthe differentiationâ€ becomes something that must be possessed in order to enter and defense among the tight competition with many competitors. From a many factors that may be influence, the creative and cultural are one of the unique factors that need to be considered. In this research, those both factors were lifted up as the independent variables to be observed further about the presence-absence or large-small impacts that appeared against the dependent variable, namely: studentâ€™s decision, in the context to choosing the desired temporary shelter. By the questionnaire mediator, this research was improved moreover systematically, and the answers of the respondents are the key decider where is these research culminates. Wherein, the multiple linear regression analysis was the chosen method in order to helping solve this problem. Through this method, was obtained a multiple linear regression equation that refers to the important information about the correlation among those three variables, which is explicitly state that the creative and cultural elements turned out have a positive influence. With the results: Fcount (54,182 > 3,091) which means that, â€œThe creative and cultural elements simultaneously influence on student's decision in choosing the desired boarding houseâ€, also tcount (4,233 > 1,984) and (2,601 > 1,984) which means that, â€œThe creative or cultural elements partially influence on student's decision in choosing the desired boarding houseâ€. Based on these final result that given, and then arranged a business model with the addition of creative and cultural elements in it, that appropriate to be able to applied at a newcomer boarding house as the main object, which also is the source problem of this business research, namely: GW Indekost. Wherein, the solutions that are meant above, among others: the waste recycle to be the new useful goods, the routine donation to be distributed to orphanages, the special privilege in phone rations to contact the parents, the adopting of eco-green principal, the alternative invoice by a pulse system, the royal exterior design with Balinese architecture, the ethnic Balinese interior design that is modern, simple and minimalist, the distinctively Balinese ornaments detail, the set of Balinese traditional music instruments, the application of vertical garden as a green area.Â Keywords: creative, cultural, studentâ€™s decision, multiple linear regression analysis,Â  business model.